Quality of Life Related to the Health of Elderly Pensioners and Non-Pensioners in Santa Marta, Colombia - Marín Monroy, Cristina; Castro Molinares, Suly (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2013)
The increase of the population of major adults generates a problematic at the social level, economically and of attention in health, parameters related with having or not a good quality of life. 177 60-year-old adults in forward of Santa Marta were studied, with a card of information demographic partner and the questionnaire SF36. Comparing the information obtained of the population pensioned and not pensioned, no significant differences were found in the dimensions Physical Role, Corporal Pain, General Health, Vitality, Social Function, Mental Health and Health in the Time. It is concluded that the quality of life of major adults of Santa Marta is good, nevertheless, some significantly different averages were found between both compared populations: it is observed that the pensioned ones demonstrate better physical function than the not pensioned ones; situation contradicts for the dimension Emotional Role, where the not pensioned ones expressed better function than the pensioned ones.